If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 8x = 6(3.14) Reorder the terms: 8x + 5y = 6(3.14) Multiply 6 * 3.14 8x + 5y = 18.84 Solving 8x + 5y = 18.84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. 8x + 5y + -5y = 18.84 + -5y Combine like terms: 5y + -5y = 0 8x + 0 = 18.84 + -5y 8x = 18.84 + -5y Divide each side by '8'. x = 2.355 + -0.625y Simplifying x = 2.355 + -0.625y
| 6.3=b-1.5 | | 2y(3y-4y+6)=4 | | 1/2-45x=225 | | -18=r-12 | | 5x/4-8=x/2+7 | | a^2+2=-1 | | 3x+6+5x+14=180 | | -3(x+2x-4)=8 | | 3+5=a | | (45+1/2)x=225 | | 32-6x+7x=15+28 | | (45+1/2x)=225 | | -6/7a=18 | | 4x-7+2=2(3x-3)-1 | | x-3/4-3=x-7/3 | | 45+1/2x=225 | | -7c=-63 | | -x(4x-3)=-1 | | (x+5)(x+1)(x-8)=0 | | -21+12c=27+6c | | -21+12c=27+6c | | X-8+4x=17 | | 7x/12-7=x/3+5 | | -x(x-7)=10 | | 5x^3-14x^2+8=0 | | (3k-1)(2k-1)=0 | | x(2x+4)=12 | | (4+y)(2y+9)=0 | | 6w^2+11w+10=0 | | 2x+3-5=3x | | -7-(-24)= | | 2n/5-3/7=13/35 |